Peran Audit Aset Tetap untuk Meningkatkan Pengendalian Internal dan Mengurangi Risiko Kerugian Perusahaan - Rusnawati, Rusnawati; A. Asharil Kahar; Masyhuri (Journal of Economic and Business Advancement, 2026)
This study examines the role of fixed asset audits in enhancing internal control effectiveness and reducing the risk of corporate losses. Fixed assets represent a significant portion of company resources and are vulnerable to misstatement, misuse, and inefficiencies if not properly controlled. The research adopts a qualitative descriptive approach through literature review and analysis of previous empirical studies related to fixed asset audits, internal control systems, and risk management. The findings indicate that fixed asset audits play a crucial role in ensuring accurate asset recognition, valuation, depreciation, and disclosure in financial statements. Effective fixed asset audits strengthen internal control by improving asset safeguarding, compliance with accounting standards, and reliability of accounting information systems. Furthermore, the integration of fixed asset audits with internal audit functions supports better risk mitigation and informed managerial decision-making. The study concludes that consistent and well-implemented fixed asset audits contribute significantly to financial reporting quality and sustainable corporate performance by minimizing asset-related risks and potential losses.